Settlement Of Electronic Integrated Liability Services - Lisza Agustina Putri (Sultan Agung Notary Law Review, 2020)
This study aims to identify and analyze the solutions to problems that arise in the implementation of integrated electronic mortgage services. The approach method in this research is sociological juridical method. The specification of this research is descriptive analytical. The data in this study are secondary data. These problems are analyzed using the theory of justice, the theory of expediency, and the theory of the legal system. Based on the results of the research that solving service problems. Security rights integrated electronically things that must be done so that no parties are disadvantaged in the problems faced, For PPAT the HT-el system needs to be repaired and upgraded to meet the provisions of laws and regulations as well as the needs in the field. It is also necessary to provide intensive counseling to all parties involved in implementing integrated electronic security rights. For Creditors, it is necessary to develop HT-e application services by utilizing the strengthening of coordination between agencies, in this context, namely the Ministry of Finance, so that the process of operating and developing services is sustainable. HT-el can be achieved by the development of HT-el services based on Human Resources (HR).